The investment environment management system in the framework of legal support as a factor of national safety - Panova, I. V.; Панова, І. В.; Andriiko, O.; Kysil, L..; Kurylo, T.; Uralova, Y.; Панова Ірина Вікторівна (Journal of Security and SustainabilityIssues. – 2020. – № 10 (1) – Р. 149-162, 2020)
Проведене дослідження дозволило не тільки провести аналіз асиметричного розвитку світової інвестиційного середовища, а й сформувати компоненти формування інвестиційного середовища країни, розділити країни на кластери за рівнем їх розвитку, відзначити факторне навантаження та запропонувати авторський рейтинг привабливості інвестиційного середовища.

The held study made it possible not only to carry out an analysis of asymmetric development of the world investment environment but also form the components of establishing an investment environment of the country, divide the countries into clusters upon the level of its development, mark factor loading, and oﬀer the authorial ranking of the investment environment attractiveness.

Проведенное исследование позволило не только провести анализ асимметричного развития мировой инвестиционной среды, но и сформировать компоненты формирования инвестиционной среды страны, разделить страны на кластеры по уровню их развития, отметить факторную загрузку и составить авторский рейтинг привлекательности инвестиционной среды.
Keywords: Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Економічні науки. Економічна безпека. Economics. Economic Security. Экономические науки. Экономическая безопасность; інвестиційне середовище; національна безпека; національна економіка; рейтинги; правозастосування; investment environment; national security; national economy; ranking; legal enforcement; инвестиционная среда